Toward an explanation of cultural differences in subjective well-being: the role of positive emotion norms and positive illusions - Kim, Hyunji; Sasaki, Joni Y. (Frontiers in Psychology, 2024)
The present research explores the role of positive emotion norms and positive illusions in explaining the higher subjective well-being observed among Europeans compared to East Asians in Canada. Specifically, we investigate the underlying psychological mechanisms contributing to the prevalence of positive self-views among individuals with European backgrounds, characterized by individualism, versus those with East Asian backgrounds, associated with collectivism. Our study compares Europeans and East Asians in Canada to determine whether cultural norms regarding positive emotions account for the elevated positive self-views and subjective well-being in Europeans. With a sample of 225 participants (112 Europeans and 113 East Asians), our findings reveal significant indirect effects of culture on subjective well-being through positive emotion norms and positive illusions. This study highlights that Europeans, compared to East Asians, believe it is more appropriate to experience and express positive emotions, and this norm influences their positive self-views, subsequently impacting subjective well-being. These findings offer valuable insights into how cultural factors shape subjective well-being across different groups.